1996
DOI: 10.1136/vr.138.18.437
|View full text |Cite
|
Sign up to set email alerts
|

Canine distemper virus in Lake Baikal seals (Phoca sibirica)

Abstract: The virus epizootic which resulted in significant mortality in Siberian seals (Phoca sibirica) in Lake Baikal during 1987/88 was caused by canine distemper virus. Sequence analysis of the virus glycoprotein genes revealed that it was most closely related to recent European field isolates of canine distemper virus. This paper presents evidence that the same virus continued to circulate in seals in Lake Baikal after the initial epizootic. Three out of 45 brain tissue samples collected from seals culled in the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…In a study examining freeranging carnivores from the Serengeti ecosystem of Africa, closely related CDV isolates were detected from four different species (9), suggesting extensive interspecies transmission. Analysis of PDV-2, which was isolated from Siberian seals, demonstrated a relationship to CDV isolates from a German dog and ferret (26), suggesting that transmission from one of these hosts may have been responsible for the widespread infection seen in these freshwater seals (27).…”
Section: Discussionmentioning
confidence: 99%
“…In a study examining freeranging carnivores from the Serengeti ecosystem of Africa, closely related CDV isolates were detected from four different species (9), suggesting extensive interspecies transmission. Analysis of PDV-2, which was isolated from Siberian seals, demonstrated a relationship to CDV isolates from a German dog and ferret (26), suggesting that transmission from one of these hosts may have been responsible for the widespread infection seen in these freshwater seals (27).…”
Section: Discussionmentioning
confidence: 99%
“…4,9 A later study showed that the same virus continued to circulate in Lake Baikal seals, years after the epizootic, with only 2-3 nucleotide differences in comparison with the original isolate. 8 The authors of that study looked at a region of the P-gene, which overlaps much of the region analyzed in this study. Similarly, 3 nucleotide differences were observed in the Alaskan sequence compared with that of the Siberian isolate of 1987-1988.…”
Section: Discussionmentioning
confidence: 99%
“…CDV strains Onderstepoort (large-and small-plaque variants OND-LP and OND-SP) and Rockborn (RB), a dog isolate from Belfast (Dog/NI) (22), and strains A75/17-V (wild-type A75/17 adapted to growth in Vero cells), BUS (Bussel), and HAN2544/95 (a gift from L. Haas and V. von Messling, Tierärz-tliche Hochschule, Hannover, Germany) were propagated using Vero cells. Briefly, Vero cells in minimal essential medium containing 5% fetal calf serum were infected at a multiplicity of infection (MOI) of 0.01 at 37°C and incubated at 37°C for 3 to 5 days, depending on when the optimal titer of infectious CDV was produced.…”
Section: Propagation Of Cells and Canine Distemper Virus Strainsmentioning
confidence: 99%
“…Canine distemper virus (CDV) causes in carnivores (canines, felids, ferrets, raccoons, and seals) a highly contagious disease with many similarities to human measles but also with a significant difference, as it is much more neurotropic and causes acute encephalitis in about half of the infected animals (2,22). The disease is characterized by fever, coryza, conjunctivitis, gastroenteritis, and pneumonitis.…”
mentioning
confidence: 99%